Hereditary angioedema caused by C1-esterase inhibitor deficiency: a case report with literature-based analysis - Athar, Sufia; Korichi, Noureddine; Siam, Yousra Shehada (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Hereditary angioedema (HAE) caused by C1-esterase inhibitor deficiency is an autosomal-dominant disease caused by a mutation in the C1-inhibitor gene. It is a rare disease that is often worsened during pregnancy and childbirth. HAE, though uncommon but if untreated it may lead to maternal death. The case report presents the successful management of a 24 years old, G2P1, with hereditary angioedema caused by C1-esterase inhibitor deficiency. This patient was managed with a multidisciplinary approach by an obstetrician, an immunologist, an anaesthesiologist and a pediatrician. She had an uneventful antenatal period, labor was induced. She had precipitate delivery and soon after delivery had a flare up of the disease. It was successfully managed with fresh frozen plasma and close observation.